Development of model to predict the compressive strength of concrete using schmidt hammer (2016)
In Nigeria and in the world at large, there are recorded cases of building and structural collapse and this is been on the increase. This implies that there is a drastic reduction in the quality assurance of construction processes and stages. Many factors: availability of compression machine and its proximity to the construction site, the technical know how in the operation of the machine, the difficulties associated with conveying concrete cubes from construction sites to the laboratory for testing, the time required for this, and the epilepsy in the power supply needed for the operation of the machine among other factors militate against the assurance of quality control. Therefore, this study considered the possibility of developing a model to predict the compressive strength of concrete using Schmidt hammer. In an attempt to develop a model to predict the compressive strength of different mix proportions, a mix proportion was carried out by the used of the mixture module of the Design Expert 10.0. Three hundred and twenty numbers of 100mm cubes of concrete were cast from the proportioned mixes with a constant water cement ratio of 0.6 and tested at day 7, 14, 21, 28 and 56 by Schmidt hammer and then by the compression strength machine. The data obtained were modeled to forecast the compressive strength of concrete with the used of Response Surface Methodology (RSM). The model was validated using different sets of concrete cubes at day 7, 14, 21, 28 and 56. The resulting two-factor interaction- 2FI model with a confidence level of about 95 % obtained is given as y = 0.40490x1 + 3.29201x2 - 0.030370x1x2- 24.21467.Where, y = compressive strength, x1 = age and x2 = rebound number. The results obtained from the validation of the model revealed that the application of the model in the prediction of compressive strength of concrete has an average of 95.2 % accuracy with very high conservative value and 4.7% deviation from the compression machine’s results. Thus, the application of Schmidt hammer in the prediction of compressive strength is effective and conservative and the results from the model can be employed in the design satisfactorily and the model can be employed in the assurance of quality control in construction sites.